Ekstraksi Jahe (Zingiberis Officinale) dan uji pemisahan Kromatografi Lapis Tipis (KLT) - Lalu Busyairi Muhsin; Muh. Eka Putra Ramandha (Biocity Journal of Pharmacy Bioscience and Clinical Community, 2023)
Ginger (Zingiberis Officinale) is a type of plant that belongs to the rhizome plant type, ginger is commonly used by the community as an ingredient for herbal drinks, based on this, it is necessary to have a simple extraction that can be used by the wider community to obtain a purer ginger extract, in this study it was conducted that the extraction or separation process of 100 grams of ginger simplicia through the maceration process yielded 27.9 grams, then a purity test was carried out using the principle of TLC (Thin Layer Chromatography) test with eluent or the mobile phase used was methanol, ethyl acetate and N hexane with a ratio of 7:7:6, and an Rf result of 0.18 was obtained based on the distance of the extraction spot divided by the distance traveled by the eluent, and the results of the TLC plate were visible using 254 nm and 366 nm UV light. Based on these results, it can be concluded that the extraction carried out on ginger simplicia was successful.